PERUBAHAN POLA KOMUNIKASI KELUARGA DI ERA DIGITAL - adel, Adelia putri agustina (FISIP UPNVJ, 2023)
Communication patterns in the family have a significant impact on relationships between family members and the psychosocial development of family members. With the development of information and communication technology, especially in the current digital era, family communication patterns have experienced quite significant changes. The digital era has brought fundamental changes in the way humans interact and communicate. At a micro level, these changes affect social relationships within the family. This change in the communication system was accompanied by an increase in media use. This research will focus on families in Bahagia Village, Babelan District, Pondok Ungu Permai, Bekasi City, because family dynamics in urban areas tend to be more influenced by technological developments. The method used in the research is descriptive qualitative. Interviews were conducted with informants of two married couples from Pondok Ungu Permai, Sunarto and Devi and husband and wife Andi and Ani. The results of this research show that digital technology can have a positive impact on family communication, facilitating long-distance interactions, enabling quick sharing of information, and helping to monitor children.